Use of benthic macroinvertebrates as bioindicators in an urban stream in Conceição do Araguaia-PA - Queiroz, Maria Elisa Ferreira de; Schäffer, Alexandre Luiz; Villela, Ana Carolyna Aparecida Silva; Martins, Danilo Epaminondas Martins e; Silva, Paulo Henrique Teles da (Sustainability in Debate, 2018)
The benthic macroinvertebrates have been used to evaluate the water quality of rivers and lakes, since their distribution and occurrence are related to different environmental factors. The aim of this study is to evaluate the environmental and water quality conditions of an urban stream in the state of Pará (Brazil), by capturing these organisms and later classifying them by the Biological Monitoring Working Party Score System (BMWP) index. This method is based on the tolerance of the organisms to the impact with the environment, generating scores to those present in the environment and by that constituting an index of water quality in the place. As a result, the 2,288 individuals collected (8 orders and 23 families), belonging to the Mollusca, Anelida and Arthropoda phyla, presented low scores and most of the points sampled (73%) were classified as contaminated, reflecting the consequences of disordered urban growth and the precarious conditions of basic sanitation that the state presents.